LABCAT: locally adaptive Bayesian optimization using principal-component-aligned trust regions - Visser, Emile (Stellenbosch : Stellenbosch University, 2025)
Visser, E. 2025. LABCAT: Locally adaptive Bayesian optimization using principal-component-aligned trust regions. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/18500d0c-a92b-49f8-80bd-37b67d81f7f2